Reducing Thermal Hysteresis in Epitaxial Ni–Mn–Ga–Co Films by Transformation Cycling - Diestel, Anett; Chekhonin, Paul; Niemann, Robert; Skrotzki, Werner; Nielsch, Kornelius; Faehler, Sebastian (physica status solidi (b), 2018)
Films are of particular interest for magnetocaloric refrigeration as they allow for a fast heat exchange. Here we report on metamagnetic epitaxial Ni–Mn–Ga–Co films, where a reduction of thermal hysteresis to 50% during several tens of temperature cycles is observed. This reduction occurs by an increase of the martensitic start temperature and thus can be attributed to a facilitated nucleation of martensite. Two mechanisms for reduction of hysteresis are identified: 1) delamination, which reduces constraints from the rigid substrate and 2) the formation of defects, which reduces the nucleation barrier. The detailed analysis and interpretation of microstructure before and after cycling gives a detailed understanding of the nucleation and delamination process.
CRIS-Team Scopus Importer:2022-04-14
Keywords: delamination; epitaxial films; hysteresis; magnetocaloric; Ni–Mn–Ga–Co